ASPEK PERSAHABATAN DALAM FILM BIG HERO 6 PRODUKSI WALT DISNEY ANIMATION STUDIOS - Lumenta, Christianto; Wantasen, Isnawaty L.; Sigarlaki, Stephani J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â The title of this research is â€œFriendship in the Film Big Hero 6 by Walt Disney Animation Studiosâ€ and it is intended as a requirement to accomplish a degree at the Faculty of Humanities Sam Ratulangi University. The aims of this study are to analyze the friendship aspect and the depiction of friendship reflected in the film Big Hero 6 through the portrayal of the characters named, Hiro, Go Go, Honey Lemon, Fred, Wasabi, dan Baymax. Theories from some experts are being applied in this study, such as theory from Dessai (2010) to unfold the definition of friendship in general and theory from Grieff (2009) to describe the elements of maintaining friendship. Â The results show that 1) the characters portray 5 friendship aspects which are solidarity, sacrifice, trust, understanding, and teamwork; (2) the depictions of friendship through some characters that are always there for Hiro; Baymax who gives his life for Hiro, the shape of trust between Hiro and Baymax, Baymaxâ€™s sensitivity of understanding the circumstances, and hand in hand to defeat the villain.Keywords: Friendship, Film, Animation, Big Hero 6.